Relationships Between Psychosocial Factors and Mental Health Among Nurses Working With COVID-19 Patients in Japan - Takashi Ohue RN, PhD; Eiichi Togo RN, MS; Yuka Ohue RN, MA; Kazuko Mitoku RN, PHN, PhD (SAGE Publishing, 2023)
Background Nurses who work with COVID-19 patients may suffer high levels of work-related stress, anxiety, and depressive symptoms. These impacts raise concerns about the deterioration of their mental health during this time. Objective This study examines the relationships between psychosocial factors (health, behavior, social, and economic factors) and mental health on among nurses working in a COVID-19 ward in Japan. Design A cross-sectional questionnaire-based study design was adopted. Methods We randomly selected 41 general hospitals that had over 400 beds. The participants were nurses who cared for COVID-19 patients at five hospitals. The questionnaire was completed by 56 nurses (seven men and 49 women) (response rate 46.6%). The survey asked participants about their basic attributes (gender, age, years of experience). It also included the Japanese version of the Patient Health Questionnaire-9, the Japanese version of the Generalized Anxiety Disorder-7, the Japanese version of the Impact of Event Scale-Revised, and the Maslach Burnout Inventory-General Survey to measure depression, anxiety, trauma experience, and burnout, respectively. To determine psychosocial factors, perception of damage from harmful rumors, nurses' intention to quit their jobs, working environment changes, and changes in daily life were measured. Results Intention to quit was specifically associated with "wanting to continue nursing," the posttraumatic stress disorder (PTSD) symptom of avoidance, depression, anxiety, and burnout. Nurses who had experienced the impact of harmful rumors in the workplace had high levels of PTSD symptoms, including intrusion, avoidance, and hyperarousal, as well as depression, anxiety disorder, and burnout cynicism. Regarding changes in the working environment, significant differences were confirmed in PTSD symptoms including intrusion, avoidance, and hyperarousal, as well as depression. We also examined the relationship between changes in daily life and mental health. We found that answering affirmatively to "the family income has decreased," "I've had family problems," and "I cannot do housework" related to mental health disorders among the nurses. Consideration: Psychosocial factors that may have been exacerbated during the COVID-19 pandemic were found to affect nurses' mental health. Thus, reducing these psychosocial factors and building a mental health support system for nurses is crucial.